Saturday

April 18, 2015

April 18, 2015

Posted by **oscar** on Friday, November 20, 2009 at 6:18am.

- Math -
**drwls**, Friday, November 20, 2009 at 6:25amy = 2(x-3)^2

(y/2) = (x-3)^2

x-3 = sqrt(y/2)

x = sqrt(y/2) + 3 is the answer.

Was the "square root" shown as a radical sign with a 2 in front? I makes no sense to write sqrt(2y/2). That would be just sqrt(y)

**Answer this Question**

**Related Questions**

Algebra - I've been trying to figure out this equation for over an hour but all ...

some algebra help (radicals) - I hope I am writing this down right.. I am trying...

Substitution Method-Plz help - Use the Substitution method to solve the system ...

physics - Okay, I have an example problem that I'm trying to solve that comes ...

math - first was w=Cr^-2 solve for r I came up with r=sqrt of C/w Now I have ...

calc - limits - I have been trying to figure out these limit problems and I get ...

Physical chemistry - help! I am trying to figure out how to convert from ...

math - what would the answer come out the be if you rationlized this equation: ...

Solving for x - ((2X-14Cos45)/(49+X^2-14XCos45))+0.3536 = 0 Solve to find the ...

Calculus (Please check my work!) - Suppose that y = f(x) = x^2 - 4x + 4. Then on...